Alaska tidewater glacier terminus positions, 1948–2012. Issue 2 (6th February 2014) - McNabb, R. W.; Hock, R.
<x xml:space="preserve">Abstract</x> A significant portion of the world's glacier ice drains through tidewater outlets, though much remains unknown about the response to recent climate change of tidewater glaciers. We present a 64 year record of length change for 50 Alaska tidewater glaciers. We use U.S. Geological Survey topographic maps to provide a base length for glaciers before 1970. Using all available cloud‐free Landsat images, we manually digitize calving front outlines for each glacier between 1972 and 2012, resulting in a total of more than 10, 000 outlines. Tidewater glacier lengths vary seasonally; focusing on the 36 glaciers terminating in tidewater throughout the study period, we find a mean (± standard deviation) seasonal variation of 60± 85 m a−1. We use these oscillations to determine the significance of interannual changes in glacier length. All 36 glaciers underwent at least one period (≥1 year) of significant advance or retreat; 28 glaciers underwent at least one period of both significant advance and retreat. Over the entire period 1948–2012, 24 of these glaciers retreated a total (± uncertainty) of 107.95±0.29 km, 11 advanced a total of 7.71±0.20, and one (Chenega Glacier) did not change significantly. Retreats and advances are highly variable in time; several glaciers underwent rapid, short‐term retreats of a few years duration. These retreats occurred after large changes in summer sea surface temperature anomalies; further study is needed to determine what triggered these retreats. No coherent regional behavior signal is apparent in the length record, although two subregions show a coherence similar to recent observations in Greenland.